2003
DOI: 10.1248/bpb.26.787
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Lipid Dynamics on the Inhibition of Bovine Brain Synaptosomal Na+-K+-ATPase Activity Induced by 4-Hydroxy-2-nonenal

Abstract: The effects of lipid hydroperoxide degradation products, such as 4-hydroxy-2-nonenal (HNE) and malondialdehyde (MDA), on bovine brain synaptosomal ATPase activities and their membrane lipid organization were examined. When the synaptosomes were treated with HNE, this resulted in the decrease of Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…38) We have recently reported that the Na ϩ /K ϩ ATPase activity of bovine synaptosomal and reconstituted membranes is markedly inhibited by interaction of the membrane constituents with 4-hydroxy-2-nonenal. 39,40) These findings also pose the possibility that the breakdown products of lipid hydroperoxides are related to the onset mechanism of Al toxicity.…”
Section: Fig 6 Effects Of Nac and Other Antioxidants On Ros Productionmentioning
confidence: 90%
“…38) We have recently reported that the Na ϩ /K ϩ ATPase activity of bovine synaptosomal and reconstituted membranes is markedly inhibited by interaction of the membrane constituents with 4-hydroxy-2-nonenal. 39,40) These findings also pose the possibility that the breakdown products of lipid hydroperoxides are related to the onset mechanism of Al toxicity.…”
Section: Fig 6 Effects Of Nac and Other Antioxidants On Ros Productionmentioning
confidence: 90%
“…HNE can lead to an alteration in the lipid dynamics of membranes, 11,12) which can affect the function of transmembrane proteins. We have recently reported that the inhibition of bovine cerebral synaptosomal Na ϩ -K ϩ -ATPase activity associated with modification of the membranes by HNE is closely related to the decreased lipid fluidity at the lipid/water interface on the membrane surface.…”
mentioning
confidence: 99%
“…,K ? -ATPase has been observed following exposure to oxygen radical generating system or to lipid peroxidation end products like 4-hydroxy-2-nonenal (Kovachich and Mishra 1981;Mishra et al 1989;Lehotsky et al 1999;Miyake et al 2003;Kadoya et al 2003).…”
Section: Discussionmentioning
confidence: 99%